2010
DOI: 10.1155/2010/494656
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the One- and Two-Year Growth Response in Children Treated with Growth Hormone: Analysis from an Observational Study

Abstract: To assess gender-, pubertal-, age-related differences in change from baseline height standard deviation score (ΔHSDS), data from 5,797 growth hormone (GH) naïve pediatric patients (<18 years) with growth hormone deficiency (GHD), multiple pituitary hormone deficiency (MPHD), Turner syndrome (TS), small for gestational age (SGA), Noonan syndrome (NS), and idiopathic short stature (ISS) were obtained from the ANSWER (American Norditropin Studies: Web-enabled Research) Program registry. For patients with SGA, Δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 27 publications
4
23
1
1
Order By: Relevance
“…Recently published ANSWER Program data on patients with Noonan syndrome with a mean referral age of 9 years showed that baseline age was negatively correlated with ΔHSDS after 1 or 2 years of GH treatment, indicating that older baseline ATS resulted in lower ΔHSDS [ 27 29 ]. In the present study, analysis of the relationship between age at initiation of GHT and near-adult HSDS in patients with GHD, ISS, and TS showed significant negative correlations, which is consistent with previous reports [ 13 , 15 , 28 ]. The results of the current analysis are among the first to describe the long-term effects of GH treatment, including an increase in HSDS at the time of NAH, in children who initiated GHT at an older age.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Recently published ANSWER Program data on patients with Noonan syndrome with a mean referral age of 9 years showed that baseline age was negatively correlated with ΔHSDS after 1 or 2 years of GH treatment, indicating that older baseline ATS resulted in lower ΔHSDS [ 27 29 ]. In the present study, analysis of the relationship between age at initiation of GHT and near-adult HSDS in patients with GHD, ISS, and TS showed significant negative correlations, which is consistent with previous reports [ 13 , 15 , 28 ]. The results of the current analysis are among the first to describe the long-term effects of GH treatment, including an increase in HSDS at the time of NAH, in children who initiated GHT at an older age.…”
Section: Discussionsupporting
confidence: 93%
“…Patients identified using HV and age criteria had sufficient visit frequency from which to assess HV consistent with NAH. As noted in previous publications from the ANSWER Program pediatric patients are generally excluded from analysis if baseline chronologic age (CA) was <1 year or >18 years, or if baseline values of key variables were missing or deemed inconsistent or implausible (e.g., lack of height information at baseline; baseline height <35 cm or >200 cm; baseline HSDS < -5 or > +2) [ 13 , 15 ]. The current study assessed children with GHD (patients with IGHD and MPHD), ISS, and TS who reached NAH after treatment with GH.…”
Section: Methodsmentioning
confidence: 99%
“…However, different from patients reported in the literature, our patients’ population received rGH therapy at an earlier age for all indications (9.0 years) compared to the French SAGhE Study (11.0 years) [ 17 ]. Also, children with GHD in our study started rGH therapy at median age of 6.4 years compared to 10.2 years from the International ANSWER Registry [ 4 ], 10.8 years from USA [ 18 ], 9.2 years from the Pfizer International Growth Database (KIGS) [ 19 ] and 8.25 years from Taiwan [ 20 ]. For children with ISS, the age of initiation of therapy in a systematic review ranged from 6.1 to 12.9 years [ 21 ] compared to 10.6 years in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data from the American Norditropin Studies: Web-Enabled Research (ANSWER) Program® also showed that pediatric patients treated with a mean starting rhGH dose of 50 μg/kg/day showed a substantial increase in HSDS after 2 years of follow-up; at the end of 2 years, the ΔHSDS was 1.0 for patients with GHD and multiple pituitary hormone deficiency [21]. In addition, the change from baseline in HSDS was greater in prepubertal than in pubertal GHD patients.…”
Section: Discussionmentioning
confidence: 99%